BIOSKOP DAN MASYARAKAT KOTA PALU, 1950-1998 - Aditama, Muhammad Reza (Manaqib: Jurnal Sejarah Peradaban Islam dan Humaniora, 2022)
This article aims to answer the following 3 questions: 1) How is the development of cinema in Palu City?; 2) How is the influence of cinema on the people of Palu City?; and 3) Why does the presence of cinema produce a new cultural identity in the people of Palu City? The problems in this article are solved using historical methodologies and anthropological approaches. The results of this study indicate that: 1) In the period between 1951-1990 the development of cinema was only in the form of an increase in number, then in 1991 there was one cinema that was different from previous cinemas so that it could create a discourse on traditional and modern cinema and the difference was the shape of the building, facilities, and film distribution network. However, without distinguishing between traditional and modern cinemas, all of them stopped operating at the end of 2000 because there were so many alternative media for film screenings; 2) Cinema as popular culture can increase and have an influence on the consumption of fashion, music, and especially films to the behavior of the people in Palu City; 3) Cinema, in the process of presenting a new cultural identity there are several phases in certain periods in society, namely initially only as popular culture (1951–1989), the second learning space (1984–1998), the third non-privacy space (1990–2000), then these three things become markers that cinema, which is only space, can form a new cultural identity in society.